C-Reactive Protein As A Response Indicator In Drug-Naïve Patients With Major Depressive Disorder: A Hospital-Based Study - Muneer, Ather; Munir, Nargis; Shams, Nadia; Inam, Mirza; Ghani, Usman; Ayub, Neelam (Journal of Rawalpindi Medical College, 2023)
Abstract Objective: C-reactive protein (CRP) is an indicator of the inflammatory process in the body, and is associated with the pathogenesis of depression through its purported effect on neurotransmitter function in the brain. Current research aims to study the relationship between the levels of CRP and the rate of remission of major depressive disorder with first-line antidepressant therapy. Methods: This hospital-based prospective study included thirty patients by purposive sampling technique. Patients with first-episode MDD with no history of antidepressant exposure and other medical comorbidity were recruited for pharmacotherapy with escitalopram, a first-line antidepressant. Patients taking antidepressants, anti-inflammatory medicines, having co-morbid conditions or other psychiatric conditions were excluded. The baseline CRP levels were measured and depressive symptoms were evaluated using the Hamilton Rating Scale for Depression (HRSD) at weeks 0, 6 and 12. The patients with low (≤5 mg/l) and high (>5 mg/l) CRP levels were compared for remission rates at week 12 using Kaplan–Meier survival analysis. Results: Amongst the 30 cases, 11(36.7%) were males and 19(63.3%) were female patients. The mean age was 35.95±7.85 years. Both groups were matched concerning age, gender, BMI and baseline HRSD score (p>0.05). As per Kaplan–Meier survival analysis, a significantly higher proportion of patients had remission of MDD at the 12th week having CRP levels ≤5 mg/l than the patients with CRP levels >5 mg/dl (p=0.002). Conclusion: This research concluded that after an adequate trial with a standard antidepressant, higher levels of CRP could lead to poorer remission rates in MDD subjects and could represent a sub-group of patients with treatment resistance.